Quantification of hydrogen isotopes by CF-LIBS in a W-based material (WZr) at atmospheric pressure: from ns towards ps. (16th November 2021) - Roldán, A Marín; Dwivedi, V; Veis, M; Atikukke, S; van der Meiden, H; Držík, M; Veis, P
Abstract: Tungsten-based materials are possible candidates as PFCs in future fusion devices. LIBS is one of the most suitable techniques for monitoring erosion and deposition processes including fuel retention, due to its versatility and ability to perform in situ measurements. By deploying ps-LIBS, instead of ns, the laser ablation occurs with fewer melting effects. This work compares ns- and ps- (CF)-LIBS characterization of WZr(D) samples, at the linear plasma generator at Magnum-PSI at the DIFFER. The laser energy has been optimized for both laser regimes, lowering the laser energy for the ns regime (from 19.9 mJ pulse −1 to 7.4 mJ pulse −1 ) to approximate to ps regime (0.3 mJ pulse −1 ). All the experimental measurements have been performed at Patm . The pure WZr samples have been analyzed in ambient air, while the WZrD sample measurements have been performed under Ar gas flow. The retained deuterium content varies from 4 at% to 0.3 at%.